Kemampuan Pemecahan Masalah Berbasis Pendekatan Realistic Mathematics Education (RME) - Tazia, Leadyania Hasbilah; Nurul Astuty Yensy; Teddy Alfra Siagian (ARITHMETIC: Academic Journal of Math, 2024)
Problem-solving ability is a student's ability to involve the process of a task whose solution method is not yet known in advance. To complete the solution, students need to map their knowledge. Building a flat-sided space is one of the materials whose solving method requires strategy and creative thinking and contains mathematical ideas or mathematical concepts. This study aims to examine the effect of the realistic mathematics education approach on students' problem-solving abilities in three-dimensional shapes at SMP Negeri 10 Kota Bengkulu. This type of research was a quasi-experimental design using a one-group pretest-posttest design. The population in this study was all grade VIII students of SMP Negeri 10 Kota Bengkulu for the 2022–2023 academic year. The sample for this study was class VIII E, which was selected using purposive sampling. The sample consisted of 30 students. Data collection in this study was carried out using a problem-solving ability description test. The data was analyzed using a paired t-test and an N-Gain score. The results of hypothesis testing obtained a value of , and the N-Gain calculation result was . Based on the results of the study, it can be concluded that there was an influence of the realistic mathematics education approach on students' problem-solving abilities in three-dimensional shapes at SMP Negeri 10 Kota Bengkulu.